What is the Model of Sharia Marketing in Islamic Microfinance Institutions? - Shulthoni, Muhammad; Hermawan Adinugraha, Hendri; Rumiyati, Eva; Imani, Fathrezza; Achmad, Dliyaudin (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2023)
The rapid growth of BMT in Indonesia has not been matched by good marketing practices in the field. The main problems of BMT are weak funding and tight competition among BMTs. This study aims to describe an analysis of the concept, implementation, and strategy of sharia marketing in BTM Jawa Tengah. This research uses a qualitative descriptive approach using a case study type of research. The object of this research is BTM Jawa Tengah. The primary data for this study is information from interviews, with employees at BTM Jawa Tengah, namely the chairman, marketing department, and cashier. The secondary data of this research are in the form of official documents, books, journals, research results, and other data that are closely related to the subject of this research. Data collection procedures carried out are by way of observation, interviews, and documentation. Data analysis in this qualitative research uses descriptive analysis. The results of this study conclude that in general the concept of Sharia marketing in BTM Jawa Tengah is Sharia-driven or is driven by Sharia as a source of law that is oriented towards meeting the needs and desires of BTM Jawa Tengah consumers and creating value for them as long as it does not conflict with the Qur’an. and Hadith. The implementation of Sharia marketing at BTM Jawa Tengah uses the characteristics of Sharia marketing that uphold fairness, honesty, and transparency regarding margin setting and profit sharing and uses the nine ethical principles of Islamic marketing, which shows that the marketing strategy at BTM Jawa Tengah is appropriate and meets the sharia marketing perspective. The Sharia marketing strategy carried out by BTM Jawa Tengah is by determining product and service market segmentation. BTM Jawa Tengah carries out marketing activities according to the target market. This is done by looking at the needs of prospective customers. The final strategy is to apply to the position and apply traditional, conventional, and Sharia marketing in combination and simultaneously. The theoretical implications of this research can strengthen existing Sharia marketing theories. Practically, the findings of this study serve as a reference for BMT managers who wish to apply the Sharia marketing model.